Utilization of HTML5-Package in the Development of Differentiated Learning in Islamic Religious Education Based on Religious Moderation: Pemanfaatan HTML5-Package dalam Pengembangan Pembelajaran Berdiferensiasi Pendidikan Agama Islam Berbasis Moderasi Beragama - Isgandi, Yiyin; Dibdyaningsih, Haris (Universitas Muhammadiyah Sidoarjo, 2025)
This research is a research and development study of the ADDIE model developed by Dick, Carey L, and Carey JO. This research aims to produce the differentiated Islamic Religious Education learning multimedia based on religious moderation assisted by HTML5-Package at the Higher Education and to determine the feasibility and effectiveness of its implementation l. Development was carried out by creating a lecturer learning video that include explanations of the main theme, learning objectives, apperception with other disciplines and real life, explanation of content differentiation, process, and results, and closing with structured or independent assignments. Higher Order Thinking Skills type practice questions are inserted in the video using HTML5-Package. This product is suitable for learning because it received an average score of 3.4375 out of a maximum score of 4 and in the Very Good category. Student and lecturer responses assessed that this product was perceived as practical, interactive, effective, efficient, quality presentation display, and added value with an average score of 3.325 in the Good category. After both assessments were combined, this product had an average score of 3.38 in the Good category. The pre-test and post-test were also deemed effective in achieving learning objectives because there was a significant increase of 48.44 points from the average test score, average N-Gain percent 88,74%, and 95% of students experienced an increase in post-test scores. So, the product was declared suitable, effective, and efficient for implementation in differentiated learning of Islamic Religious Education based on religious moderation.